The Impact of Digital Promotion, Product Quality, Product Price, and Business Location on Purchase in MSMEs in The Coastal Region - Yulistiawan, Bambang Saras; wirawan, Rio; Puspita Dewi, Catur Nugrahaeni; Hananto, Bayu (JISA(Jurnal Informatika dan Sains), 2023)
This study aims to examine the influence of digital promotion, product quality, product prices, and business location on purchasing decisions for products produced by micro, small, and medium enterprises (MSMEs) in Pabean Udik village, Indramayu district. Pabean Udik village is located in a coastal area with relatively low levels of education and technological literacy. The study population includes MSME actors, community members, and stakeholders in the village. The measurement scale used is a Likert scale. If the model includes intervening or moderating variables, it can be analyzed using path analysis. Path analysis allows for the examination of direct and indirect relationships between variables. The analysis will help in making decisions based on hypothesis testing. The findings show that product quality has a positive effect on purchase decisions, product price does not significantly influence purchase decisions, digital promotion has a positive effect on purchase decisions, and business location does not significantly influence purchase decisions. Additionally, product quality, through business location, has a positive effect on purchase decisions, and product price, through digital promotion, also has a positive effect on purchase decisions. Digital promotion has the strongest influence on customers' purchasing decisions. To enhance the competitiveness of MSMEs in coastal areas, it is recommended to utilize digital promotions through platforms such as WhatsApp and Facebook. Additionally, programs for improving the digital literacy and skills of MSMEs' human resources are recommended to better adapt to social media and digital platforms. The aim is to increase their positive competitiveness in the market.